Development and In vitro Evaluation of Rosuvastatin Tablets by Floating Drug Delivery System (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Rosuvastatin has been the most widely used antihyperlipidemic drug. The present investigation concerns with the development and evaluation of single unit gastro-retentive drug delivery system of the hyperlipidemic drug to increase the gastric residence time and to prolong the drug release. Materials and Methods: The floating tablet of rosuvastatin was developed using gas-forming agents such as sodium bicarbonate and citric acid and gel-forming agents such as hydroxypropyl methylcellulose (HPMC) E50 and carbopol 934 with different drugs to polymer ratio by direct compression method. The prepared tablets were evaluated for their physical characteristics, namely, hardness, friability, drug content, buoyancy, buoyancy lag time, and swelling index. Further, tablets were studied for in vitro drug release characteristics for 12 h. Results and Discussion: From the in vitro release studies, the formulation F3 (2:1 ratio) showed 96.31% drug release at the end of 12 h and exhibited optimum floating lag time. A decrease in release rate of the drug was observed on increasing polymer ratio and also by increasing viscosity grades of the polymer (HPMC). Drug release from floating tablets was sustained over 12 h with buoyant properties. Based on the release kinetics, all formulations best fitted the Higuchi, first-order model, and non-Fickian as the mechanism of drug release. Conclusion: The overall result indicated that the formulation F3 containing HPMC E50 and carbopol 934 is fulfilling the needs of the gastro-retentive floating tablets of the antihyperlipidemic drug.